Environmentally compatible low-budget technology of organic waste disposal during wartime and under problems of housing and community management for individuals and local communities. - Sabo, Andrii; Сабо, Андрій Георгійович (My University, 2023)
The article examines the expediency of implementing an environmentally compatible low-budget technology for the disposal of organic waste in wartime conditions and service problems of communal services, suitable for use in auxiliary farms and at the level of local communities. The author shares his personal experience of construction and operating low-budget bioreactors suitable for use in the conditions of subsidiary farms and local communities.
Екологічно малобюджетна технологія утилізації органічних відходів у військовий час та за проблем житлово-комунальне управління особи та місцевих громад.
Keywords: organic waste; composting; bioreactor; operation; технологія утилізації органічних відходів; текологічна технологія утилізації органічних відходів